Combination of Gilbert's syndrome and gastrointestinal diseases - G. M. Dubrovina; O. K. Botvinyev; A. I. Kolotilina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To detect relation between Gilbert's syndrome (GS) and other diseases of a gastrointestinal tract (GIT).Key points. Gilbert's syndrome - hereditary, unconjugated jaundice related to decrease of activity of uridinediphosphate glucuronosyltransferase 1А1 (UGT 1А1) in the liver. The prevalence in European countries of reaches 9 %. Mutation of encoding gene — A (TA) 7TAA A is the principal cause of insufficiency of this enzyme, however development of clinical syndrome and severity of symptoms is related to other factors as well (male gender, additional genetic mutations, et al.). Provoking factors of jaundice attacks include fasting, infectious diseases, overstrain, effect of drugs and xenobiotics. Patients demonstrate various complaints related to disorders — nausea, decrease of appetite, heartburn, epigastric pain, defecation disorders. Gilbert's syndrome quite often is combined to of the upper gastro-intestinal diseases (gastroduodenitis, esophagitis, sphincter disorders). Recent studies have demonstrated, that this hereditary syndrome is a risk factor of gallbladder diseases, including biliary sludge, gallstone disease. Lower gastro-intestinal disorders often have functional origin. In the literature publications on rare frequency of colorectal cancer and Crohn's disease in patients with GS have appeared. The protective role of unconjugated bilirubin in relation to various diseases - cardio-vascular, autoimmune, oncologic is studied.Conclusion. The reasons of development of symptoms related to gastro-intestinal organs in patients with Gilbert's syndrome are investigated insufficiently. It can be assumed, that there is combination to other gastro-intestinal diseases. Diseases of the esophagus, stomach, duodenum and biliary tracts decelop most frequently at GS. To author’s opinion and literature data, it is caused by embryogenetic affinity and functional relation between liver, biliary tract and upper gastro-intestinal tract, disorder of structure and rheologic properties of bile, characteristic for GS, and also decrease of detoxification liver function. Doctors should be concerned in relation of gastro-intestinal diseases GS.